Cytology of uterine cervix after one year use of Depo Provera and Cyclofem - Jan Pieter Kambu (Indonesian Journal of Obstetrics and Gynecology, 2009)
Objective: The objective was to examine cervical cytology findings from conventional Pap smear examination in Depo-Provera® and Cyclofem® acceptor in one-year period. Method: The study design is descriptive observational involving 35 Depo-Provera® and 35 Cyclofem® acceptor. We follow up their cytology findings prospectively. This study was conduct in FER and gynecology clinics at Dr. Kariadi Hospital Semarang also at Halmahera and Ngesrep public health service. The subjects were women, aged 20 - 40 years old who chosen Depo-Provera® and Cyclofem® as their contraceptive methods. This study began on December 2006, all subjects who met inclusion criteria underwent initial cytology screening. On December 2007, and there were 70 subjects. They underwent cytology examination at month sixth (simultaneously with third Depo-Provera® injection and seventh Cyclofem® injection) and at month twelve (simultaneously with fifth Depo-Provera® injection and thirteenth Cyclofem® injection). Distribution frequency was analyzed using univariate analysis and data shown as mean and standard deviation whereas bivariate analysis was conduct with X2 and t-test. Cytology examination was conduct in anatomy pathology laboratory at Medicine Faculty, Diponegoro University/Dr. Kariadi Hospital, Semarang. Result: Inflammation rates tend to increase on Depo-Provera® group compare to Cyclofem® group. At first cytology result there is no difference between two groups, it suggest that both groups had same baseline characteristic. Thereafter, at second and third examination, Depo-Provera® group significantly showed higher inflammation and dysplasia rates compare to Cyclofem® group. Conclusion: After one-year period, there was difference on cervical cytology results that is inflammation rates which higher on Depo- Provera® acceptor compare to Cyclofem®. [Indones J Obstet Gynecol 2009; 33-4: 233-8] Keywords: pap smear, Depo-Provera®, Cyclofem®, Pap smear on hormonal contraception